2012
DOI: 10.1039/c2cs35145e
|View full text |Cite
|
Sign up to set email alerts
|

A building block strategy to access sulfur-functionalized polyoxometalate based systems using {Mo2S2O2} and {Mo3S4} as constitutional units, linkers or templates

Abstract: The present tutorial review reports on the synthetic approaches for the formation of "polyoxothiometalate" compounds with special emphasis on the unique reactivity of the preformed sulfur-containing cationic building blocks {Mo(2)O(2)S(2)}(2+) and {Mo(3)S(4)}(4+) toward polyoxometalate building blocks. Such simple chemical systems, based on chemical and structural complementarities between ionic reactive moieties have led to the synthesis of a series of relevant clusters with unrivalled large nuclearity struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 105 publications
5
75
0
1
Order By: Relevance
“…The complex [Ir(phen)Cl 4 ]cation can be a source of the {Ir(phen)} 3+ moiety for the incorporation into the structures of different polyoxometalates (polynuclear metal oxide complexes), which are now a key line in the development of modern inorganic chemistry [34,35]. The attention to the complexes with precious metals is special due to their activity in catalytic processes and, in particular, in the process of photocatalytic water cleavage [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…The complex [Ir(phen)Cl 4 ]cation can be a source of the {Ir(phen)} 3+ moiety for the incorporation into the structures of different polyoxometalates (polynuclear metal oxide complexes), which are now a key line in the development of modern inorganic chemistry [34,35]. The attention to the complexes with precious metals is special due to their activity in catalytic processes and, in particular, in the process of photocatalytic water cleavage [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…[10] The X-ray diffraction analysis revealed a sandwich-like cluster (Figure 1, a) consisting of two equivalent {SbW 9 O 33 } subunits linked by three equiva- [a] 0.0461 0.0969 R w (F 2 ) [b] 0.1361 0.2446 GOF 1.181 1.019 junction. In addition, a potassium ion is located within the sandwich-like arrangement and interacts with four terminal oxygen atoms belonging to the two {SbW 9 The three {Mo 2 O 2 S 2 } units lie parallel, forming a close, compact arrangement characterized by short S-S separations [S···S 3.563(9) Å] typical of van der Waals contacts.…”
Section: Structure Of Compoundsmentioning
confidence: 99%
“…[10] Solution studies combined with structural characterizations in the solid state showed that weak electrostatic interactions involving alkali cations govern the self-assembly process. [12] B-α-Na 9 6 ] 2+ in a ratio of 2:3 in aqueous solution at pH 4. The initial aim of this work was to extend this series of compounds to the antimony analogues constructed from the B-α-[SbW 9 O 33 ] 9trivacant anion.…”
Section: Synthesis Of the Anions And 183 W Nmr Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] However, the transformation of ap olyoxometalate core in silver(I) alkynyl or thiolate nanosized cage clusters has not been reported to date.B yrestriction inside an anosized cage,t he transformation of the polyoxometalate core may modulate the properties of the external silver(I) alkynyl or thiolate shell, and possibly lead to new POM/organosilver(I) functional materials. [21] However, the transformation of ap olyoxometalate core in silver(I) alkynyl or thiolate nanosized cage clusters has not been reported to date.B yrestriction inside an anosized cage,t he transformation of the polyoxometalate core may modulate the properties of the external silver(I) alkynyl or thiolate shell, and possibly lead to new POM/organosilver(I) functional materials.…”
mentioning
confidence: 99%